A Study on the Effects of Multiwall Carbon Nanotubes on Dynamic Stiffness of Hydrophilic-base Magnetorheological Gel - Kim, Young-Keun; Kim, Jangheon; Jang, Daeik; Kim, Soohyun; Jung, Wonsuk (Current Nanoscience, 2019)
Background: Recently, addition of multi-walled-carbon-nanotubes (MWCNTs) has been researched to enhance the rheological properties of magnetorheological (MR) materials of fluid, elastomer and gel. However, there is a lack of study on the effects of MWCNTs on hydrophilic based MR gels (MRG), which have shown a high potential to be applied in smart vibration control systems. Objective: This study is aimed to analyze the effect of MWCNTs on the dynamic stiffness of hydrophilic based MRG. Method: Dynamic stiffness of hydrophilic based MRG was experimentally computed under different magnetic fields and strain amplitudes. Results: Experimental results indicate that the addition of MWCNTs in hydrophilic MRG showed overall degradation of stiffness variation in contradictory to similar research performed on silicon oil based MR gel. Conclusion: These contradictory results reveal that MRGs of hydrophilic base have a different interaction with MWCNTs than hydrophobic oil base.
Keywords: Magnetorheological gel